ABCA7 rare variants and Alzheimer disease risk. (7th June 2016) - Le Guennec, Kilan; Nicolas, Gaël; Quenez, Olivier; Charbonnier, Camille; Wallon, David; Bellenguez, Céline; Grenier-Boley, Benjamin; Rousseau, Stéphane; Richard, Anne-Claire; Rovelet-Lecrux, Anne; Bacq, Delphine; Garnier, Jean-Guillaume; et al.
Abstract : Objective: To study the association between ABCA7 rare coding variants and Alzheimer disease (AD) in a case-control setting. Methods: We conducted a whole exome analysis among 484 French patients with early-onset AD and 590 ethnically matched controls. Results: After collapsing rare variants (minor allele frequency ⩽1%), we detected an enrichment of ABCA7 loss of function (LOF) and predicted damaging missense variants in cases (odds ratio [OR] 3.40, 95% confidence interval [CI] 1.68–7.35, p = 0.0002). Performing a meta-analysis with previously published data, we found that in a combined sample of 1, 256 patients and 1, 347 controls from France and Belgium, the OR was 2.81 (95% CI 1.89–4.20, p = 3.60 × 10 −7 ). Conclusions: These results confirm that ABCA7 LOF variants are enriched in patients with AD and extend this finding to predicted damaging missense variants.